Effect of watering on incidence of self-pruning in lime (Citrus × aurantiifolia (Christm.) Swingle) - Elda Kristiani Paisey; Edi Santosa; Ani Kurniawati; Supijatno Supijatno; Marlin Sefrila; Besse Amriati; Anjeli Sulistianti Paisey; Hayu Siwi Pribadi; Darius Dare; Nurlailah Nurlailah; Zarima Wibawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2026)
The process of self-pruning represents a form of self-destruction among shaded or diseased branches, which has the potential to deplete the resources of the tree. This phenomenon is also observed in natural ecosystems. The self-pruning mechanism can be exploited to reduce the cost of pruning in cultivated plants, such as lime trees. The objective of this study was to ascertain the mechanisms that occur during self-pruning in response to drought and flooding induction. The experiment was arranged in a randomized complete block design (RCBD) with three replications. Each replication contained three plants, giving a total of 45 plants. Samples were taken from three plants per treatment. The treatments comprised irrigation at field capacity, irrigation every day, irrigation every three days, irrigation every five days, and irrigation every seven days, and the data were analyzed using the Duncan Multiple Range Test at the 95% level. The secondary, tertiary, and quaternary branches that experienced self-pruning due to drought and flooding treatments had average lengths ranging from 3.06 to 9.53 cm and diameters between 0.50 and 1.84 mm. The physiological responses, including the photosynthetic rate, showed that both drought and inundation treatments led to a decrease in stomatal conductance and transpiration. Furthermore, the concentrations of ethylene, abscisic acid, and proline increased markedly after seven months of treatment-induced self-pruning. Keywords: abscisic acid; ethylene; proline